Combined effect of xanthan gum and water content on physicochemical and textural properties of gluten-free batter and bread. (September 2018) - Encina-Zelada, Christian R.; Cadavez, Vasco; Monteiro, Fernando; Teixeira, José A.; Gonzales-Barron, Ursula
Abstract: The objective of this study was to evaluate the combined effect of xanthan gum (XG) on physicochemical, rheological and textural properties of gluten-free batter and bread. To prepare gluten-free batter, different levels of XG (1.5, 2.5 and 3.5%) and water (90, 100 and 110%) were added to a base formula of rice (50%), maize (30%) and quinoa flours (20%); and the batters were evaluated in a factorial design. Several properties on both batter (stickiness and back extrusion) and its corresponding bread (loaf specific volume, baking loss, water activity and pH, texture profile, mean cell area, mean cell density, cell size uniformity, void fraction, mean cell compactness and mean cell aspect ratio) were then evaluated. Higher XG doses (p < .001) tended to produce batters of lower stickiness, adhesion and cohesive-strength, yet, of higher firmness, consistency, cohesiveness and viscosity index. After baking, these loaves presented lower specific volume; lower crumb aw, pH, hardness, springiness, mean cell area and void fraction; and higher (p < .001) chewiness, resilience, mean cell density, cell size uniformity and mean cell compactness. The sticker and less consistent batters produced with higher WC rendered larger bread loaves of softer and more springy/resilient crumbs with greater mean cell size and void fraction. Gluten-free loaves of good appearance in terms of higher specific volume, lower crumb hardness, higher crumb springiness, and open grain visual texture were obtained in formulations with 110% WC and XG doses between 1.5 and 2.5%. Abstract : Graphical abstract Unlabelled Image Highlights: Effects of xanthan gum and water content on gluten-free bread were studied. Rice, maize and quinoa flours were used in gluten-free formulations. Stickier batters produced loaves of higher volume and softer crumb. Higher water content produces crumb of greater porosity and open texture. 1.5–2.5% xanthan gum with 110% water produced acceptable GF loaves.